Mucocutaneous manifestations of Behçet’s disease: Pathogenesis and management from perspectives of vasculitis - Kim, Doyoung; Nakamura, Koichiro; Kaneko, Fumio; Alpsoy, Erkan; Bang, Dongsik (Frontiers in Medicine, 2022)
Behçet’s disease (BD) is a systemic inflammatory disorder characterized by vasculitis affecting blood vessels of any caliber or type. It can present with a wide spectrum of vasculitic lesions, including erythema nodosum-like lesions and retinal vasculitis, and may also lead to larger vessel diseases, such as aortic aneurysm and deep vein thrombosis. The full etiology of BD remains unclear, but it is considered a polygenetic disease with multiple genetic risk factors that promote immune dysregulation and thrombophilia. Inflammation can be triggered by environmental factors, such as bacteria or viruses, and the dysregulation of innate and adaptive immune cell subsets. Neutrophils and lymphocytes are the primary players involved in BD pathogenesis, with specific innate (i.e., neutrophil-derived reactive oxygen species and neutrophil extracellular traps) and adaptive (i.e., anti-endothelial cell antibodies) processes inducing endothelial cell activation and chemotaxis of inflammatory cells, leading to coagulation and vasculitis. These inflammation-induced vasculitic or vasculopathic features are observed in most mucocutaneous BD lesions, although vasculitis per se is often pathologically evident only during a brief period of the disease process. Due to the multifactorial nature of BD-associated inflammation, broad-spectrum anti-inflammatory medications, including glucocorticoids and immunosuppressive drugs, have been the mainstay for managing BD. In addition, inhibitors of interleukin (IL)-1, tumor necrosis factor (TNF)-α, and IL-17, which target innate and adaptive immune functions dysregulated in BD, have emerged as promising new therapeutics. In this review, we discuss the muco-cutaneous manifestations of BD by focusing on the underlying vasculitic components in their pathologies, as well as the current array of treatment options.